2b-66=6

Simple and best practice solution for 2b-66=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2b-66=6 equation:



2b-66=6
We move all terms to the left:
2b-66-(6)=0
We add all the numbers together, and all the variables
2b-72=0
We move all terms containing b to the left, all other terms to the right
2b=72
b=72/2
b=36

See similar equations:

| -15=3r | | 2r+35=71 | | 2+2v=16 | | -(u*u)+6u−3=0 | | 4s+21=89 | | 8y-y+1=15 | | W+0.8w=135 | | -u2+6u−3=0 | | -10=2v-4 | | -3(1+5n)+9(2n-8)=6n-3n | | 3(x-1)-2(5x+2)=7 | | 9x+14=9x+5 | | 0=-16t^2+12t+120 | | 36+6n=12n | | 13=y/5-17 | | 3x-2+5x+7=21 | | 8x-7=2(2x-7)-5 | | s/6=2.5 | | 4x-50+(x+22)=180 | | 4x-50+x+22=180 | | b+16=6 | | b-16=6 | | 4/37x+8/37=20/37 | | 1/3x+3/4x=91 | | 3^4x-5=27^x+2 | | c+9.25=23.25 | | K+8/3=x2 | | 3/34x+9/34=9/34 | | c-9.25=23.25 | | c/9.25=23.25 | | -2h+2=-h-13 | | 9.25c=23.25 |

Equations solver categories